Durable response to low-dose pralsetinib in a renal insufficient patient with NSCLC harboring concurrent CCDC6-RET, LINCO1264-RET, and SEMA5A-RET fusions: A case report. Issue 47 (25th November 2022) - Gu, Linping; Ji, Wenxiang; Xu, Yunhua; Han, Yuchen; Jian, Hong
Abstract : Introduction: RET -rearranged fusions have been considered as oncogenic drivers in 1% to 2% of non-small cell lung cancers (NSCLC). ARROW study has demonstrated a new selective RET tyrosine kinase inhibitors (TKIs) shows remarkable and durable responses in RET -rearranged NCSLC. In this study mainly recruited patients with common fusion partners KIF5B and CCDC6 . There is still a lack of definitive conclusions about effective of rare RET fusion variants to anti-RET therapies. Case report: A Chinese 58-year-old female renal insufficient patient with no history of smoking was diagnosed as stage IIIA (T2N2M0) lung adenocarcinoma. Next-generation sequencing targeting 520 cancer-related genes was performed on the pleural effusion samples and revealed 2 novel RET fusions LINCO1264-RET and SEMA5A-RET, concomitant with a common CCDC6-RET. Management and outcome: The patient was first treated with multiple lines of chemotherapy and switched to lenvatinib but failed to respond. Due to renal insufficiency, she subsequently received pralsetinib with gradually reduced dosages (400 mg-300 mg-200 mg-100 mg qd) and achieved a partial response (PR) lasting for more than 10 months, accompanied by the declined allele frequencies of all 3 RET fusions. Discussion/conclusions: We reported the first case of the pralsetinib efficacy in NSCLC with 3 concurrent RET fusions. Our case also indicates the sensitivity of the newly identified RET fusions to this RET selective inhibitor pralsetinib, and highlights the low-dose treatment option for patients with renal insufficient background.